The Effect of Service Quality on Consumer Satisfaction at Ambarawa Traditional Market - Ardoko, Prono; Wijayanto, Yeremia; Hapsari, Pamungkas (Indonesian Journal Economic Review (IJER), 2025)
This study aims to determine the effect of tangible factors on consumer satisfaction at Ambarawa Traditional Market, to examine the influence of reliability on consumer satisfaction at Ambarawa Traditional Market, to explore the impact of responsiveness on consumer satisfaction at Ambarawa Traditional Market, to analyze the effect of assurance on consumer satisfaction at Ambarawa Traditional Market, and to understand the influence of empathy on consumer satisfaction at Ambarawa Traditional Market. This research utilizes a quantitative descriptive approach, describing the factual conditions based on collected data and questionnaires from direct field observations. The population in this study includes the customers of Ambarawa Traditional Market during the months of June, July, and August. A sample of 35 participants was selected. The analysis was conducted descriptively using frequencies and percentages, as well as Multiple Linear Regression analysis. The findings of this study indicate that tangible factors significantly influence consumer satisfaction. Reliability has a significant effect on consumer satisfaction. Responsiveness significantly affects consumer satisfaction. Assurance significantly impacts consumer satisfaction. Empathy also significantly influences consumer satisfaction. This study is beneficial for both internal and external evaluations for all stakeholders at Ambarawa Traditional Market.